Zapleti in izidi rehabilitacijske obravnave bolnikov po možganski kapi zaradi disekcije vratne arterije - Bucik Kajin, Irena (Rehabilitacija (Ljubljana), 2015)
Background: Dissection of the cervical arteries (DCA) is a major cause of ischemic stroke in young adults. The aim of our study was to determine how many patients after stroke caused by DCA were admitted for the first time to the hospital rehabilitation programmes at the University Rehabilitation Institute in Ljubljana (URI) during the last five years, what were the results of the rehabilitation of these patients, and whether any complications occurred during the rehabilitation. Methods: Our retrospective research included all the patients with stroke due to DCA who were admitted for the first time to inpatient rehabilitation at the URI in the period from November 2008 to January 2014. We collected data on the patient's age, gender, time from stroke onset to admission to the URI, duration of hospitalisation at the URI, the type of DCA, type of stroke and the presence of arterial hypertension. We searched for information on complications due to DCA. The patients' functional status was assessed at admission and at discharge using the Functional Independence Measure (FIM). We also collected data about the eventual rehabilitation at our Centre for Vocational Rehabilitation, and return to work or school. Results: The average age of the 20 patients (15 men and 5 woman) was 40 years. Eighteen patients had spontaneous DCA, two traumatic DCA. Eighteen patients experienced ischemic stroke, two from intracerebral haemorrhage. Five patients had arterial hypertension before DCA. Thirteen patients did not have complications. No patients had any recurrences of ischemic events or DCA. Functional outcome was on average good. Twelve patients were enrolled in vocational rehabilitation during the medical rehabilitation, five of them have returned to work and one to school. Conclusion: Cervical artery dissection is increasingly recognised as an important cause of stroke in young adults thanks to the development of imaging investigation methods. Complications in the subacute period when patients are involved in intensive rehabilitation programs are rare. Rehabilitation treatment of these patients is safe when precautionary measures are regarded. Prognosis of recovery is good with a good functional outcome.
Keywords: cervical artery dissection; complication; disekcija vratnih arterij; izid rehabilitacije; možganska kap; rehabilitation outcome; Stroke; zapleti